The use of relative price evaluation formulae in the UK housing sector and the extent to which these comply with English law - Rees, Rebecca (2025)
Despite the importance of the price tendered to the contracting authority for a public goods, work or service contract, and its determinative impact on the ultimate outcome of a procurement process, how price is evaluated and, in particular, the problems caused by the use of relative price evaluation formulae have not thus far received comprehensive scrutiny in the field of public procurement law.